A retrospective observational study of traumatic orthopaedic: related infections in Cambodia - Antony, Suresh J.; Faix, Dennis; Gollogly, James G.; June, Kim Yong; Oy, Heang; Savuth, Chin; Chonthida, Supaprom; Putnam, Shannon D. (International Journal of Research in Orthopaedics, 2020)
Background: The objective of this study was to establish the type of microbiology along with antimicrobial resistance related to orthopedic related trauma infections in this area in order to help guide diagnosis and treatment regimens. Methods:This study evaluated the microbial etiology of orthopedic-related infections (ORI) between September 2015 and September 2016 in three tertiary hospitals in Phnom Penh, Cambodia. Clinical records were for clinical features and demographics. Standard laboratory bacteriology was used to recover, identified and perform antibiotic susceptibility testing (AST) by disk diffusion or broth microdilution. Results:119 patients were categorized as ORI cases. In the cases identified, median interquartile range (IQR) age was 38 (IQR: 26-46) years and 80.0% were male. Of the 119 ORI cases, a total of 156 bacterial strains were recovered, identified and after review, 128 of these pathogenic bacterial strains underwent AST. Among the gram-positive pathogens, the following susceptibilities were as follows: Staphylococcus aureus (n=57) (Methicillin-resistant S. aureus (n=35; 61.4%), (Methicillin‐sensitive S. aureus (n=22; 38.6%)), coagulase-negative staphylococcus (all MS-CoNS; n=6) and four isolates of Enterococcus sp. (non-VRE). A total of 44 gram-negative pathogens were recovered and AST was performed. Among these 44, a total of nine extended-spectrum beta-lactamase (ESBL) producing strains (20.5%) were discovered including Escherichia coli (n=8), Klebsiella pneumoniae (n=1) and carbapenemase-resistant Enterobacteriaceae (CRE) (Morganella morganii). In addition, a single E. coli isolate contained both the ESBL and CRE genotypes was noted. Conclusions:This data suggests that ORI rates in Cambodia appear to be comparable to other studies in the literature. However, further studies need to be done in order to establish definitive data related to orthopedic infections in the region.